2020
DOI: 10.3390/ijms21051742
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Genetics System for the Israeli Acute Paralysis Virus and Chronic Bee Paralysis Virus

Abstract: Honey bee viruses are associated with honey bee colony decline. Israeli acute paralysis virus (IAPV) is considered to have a strong impact on honey bee survival. Phylogenetic analysis of the viral genomes from several regions of the world showed that various IAPV lineages had substantial differences in virulence. Chronic bee paralysis virus (CBPV), another important honey bee virus, can induce two significantly different symptoms. However, the infection characteristics and pathogenesis of IAPV and CBPV have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Moreover, crude bee preparations also contain host cellular material that can independently or in synergy with either the inoculated or resident background viruses to influence the virus infection dynamics. An alternative approach would be to synthesize the virus of interest in vitro (Lamp et al, 2016;Ryabov et al, 2019;Seitz et al, 2019;Jin et al, 2020;Yang et al, 2020) thereby ensuring the highest level of purity. Both cell cultures and reverse genetics also allow virus to be produced that is free of contaminants, while reverse genetics also has the option of introducing specific genetic changes to the virus genome (Lamp et al, 2016;Ryabov et al, 2019;Jin et al, 2020).…”
Section: Sources Of Virus Inoculummentioning
confidence: 99%
“…Moreover, crude bee preparations also contain host cellular material that can independently or in synergy with either the inoculated or resident background viruses to influence the virus infection dynamics. An alternative approach would be to synthesize the virus of interest in vitro (Lamp et al, 2016;Ryabov et al, 2019;Seitz et al, 2019;Jin et al, 2020;Yang et al, 2020) thereby ensuring the highest level of purity. Both cell cultures and reverse genetics also allow virus to be produced that is free of contaminants, while reverse genetics also has the option of introducing specific genetic changes to the virus genome (Lamp et al, 2016;Ryabov et al, 2019;Jin et al, 2020).…”
Section: Sources Of Virus Inoculummentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 2, 2022. ; https://doi.org/10.1101/2022.03.02.482613 doi: bioRxiv preprint the immune genes involved in the significant immune pathways of honey bee on a large scale [21]. Our results showed that Toll pathway was mainly activated for defending against viral infection of honey bees.…”
Section: Introductionmentioning
confidence: 72%
“…The stepwise cloning strategy for developing the full-length cDNA clone of IAPV was conducted according to Yang et al [21]. Briefly, viral RNAs were extracted from purified IAPV above using viral RNA kits (QIAGEN) and three fragments covering the full-length genome were synthesized with high-fidelity Phusion HiFi PCR Master Mix (NEB,) using specific primers as shown by Yang et al [21]. Plasmid pACYC177 (New England Biolabs, Ipswich, MA) was used to clone three fragments and a T7 promoter sequence (TAATACGACTCACTATAGGG) was linked at the 5′ end of the first fragment.…”
Section: Generation Of An Infectious Clone Of Iapvmentioning
confidence: 99%
“…Constructing the infectious clone of IAPV and RNA synthesis were performed as previously described [ 29 ]. In brief, the full-length genome of IAPV was amplified from bee samples collected in our experimental apiaries using RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the full-length genome of IAPV was amplified from bee samples collected in our experimental apiaries using RT-PCR. Three fragments of IAPV were amplified with high-fidelity Phusion HiFi PCR Master Mix (NEB, Ipswich, MA, USA) using specific primers [ 29 ]. A low copy vector, pACYC177 (CWBio, Beijing, China), was used to generate a stable clone.…”
Section: Methodsmentioning
confidence: 99%